PANDANGAN PEMUDA KRISTEN TERHADAP PERNIKAHAN USIA MUDA - Jusnia Yusuf Sumbung; Desriyanti Tandiama, Mildawati, Alsi Limbong, Junalia Olga Sallata (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Christian youth's views on young marriage are a relevant issue in the context of social change and traditional values in society. This research aims to explore the perceptions of young Christians towards the phenomenon of young marriage, with a focus on the theological, social and cultural factors that influence their views. The method used is a qualitative study with in-depth interviews with Christian youth in certain communities. The research results show that the majority of Christian youth view young marriage as a risky step, especially in relation to emotional, financial and spiritual readiness. They also emphasized the importance of planning and maturity in building a family based on the values of the Christian faith. However, this view is influenced by family environment, church education, and local traditions. This research recommends a pastoral and church education approach to increase awareness of the importance of readiness in marriage